ANALYSIS OF FATTY ACIDS IN VIRGIN COCONUT OIL FRYING AT VARIOUS TEMPERATURES - Pramitha, Dewa Ayu Ika; Karta, I Wayan (JST (Jurnal Sains dan Teknologi), 2021)
Fatty acid content from virgin coconut oil (VCO) is a medium-chain triglyceride (MCT) group. MCT is stable at very low and high temperatures, and the color does not turn black due to the addition of heat so that it can be developed into beneficial cooking oil for health. Therefore, a study was conducted on the content of fatty acids in VCO after being heated at temperatures of 150, 200, and 250Â°C for 60 minutes. Analysis of fatty acid content in control VCO(T0), VCO with heating temperatures of 150oC(T1), 200oC(T2), and 250oC(T3) was performed with GCMS QP-2010 Ultra.The results showed that there were differences in levels and types of fatty acids in VCO by treating T0, T1, T2, and T3. At these three temperatures still produce medium-chain saturated fatty acids and trans fatty acids are not produced, so that VCO can be utilized as cooking oil that has better stability and benefits for health.